Insecticide toxicity on the adult German ceki'oach, Blattella germanica (L.) (Dictyoptera: Blattellidae) - -Yang Lee, Chow; -Heng Yap, Han; Long Chong, Ngo- (Malaysian Journal of Science, 1996)
Thirteen insecticides (alpha-cypermethrin, beta-cyfluthrin, bendiocarb, bifenthrin, chlorpyrifos, cypermethrin, cyphenothrin, deltamethrin, etofenprox, fenitrothion, lambda-cyhalothrin, permethrin and propoxur) were tested topically against susceptible adult German cockroaches. Lambda-cyhalothrin was the most toxic compound against both sexes, while propoxur and bendiocarb were the least toxic to male and female, respectively. The Type II pyrethroids is the most toxic group of insecticide, fol-lowed by Type I pyrethroids, organophosphates and carbamates. Four factors (age, pre-treatment starvation, immobilizing techniques, and time of insecticidal application) affected adult male suscepti-bility to propoxur; however, susceptibility to deltamethrin was in-dependent from the last two factors.